KEBIJAKAN PENDANAAN DAN DIVIDEN DENGAN PENDEKATAN INVESTMENT OPPORTUNITY SET - Christian Herdinata (Jurnal Keuangan dan Perbankan, 2009)
This research aimed to identify policy difference of debt and dividend policy amongcompanies having potency high and low growth with approach of investment opportunity setin Indonesia Stock Exchange (BEI). To classify company growth, it was applied five proxiesInvestment Opportunity Set (IOS) that was market to book of asset ratio (MVE/BE), price earningratio (PER), value book of plant, property, and equipment to asset ratio ( PPE/BVA) and capitaladdition to book of asset ratio (CAP/BVA). The variables were analyzed using common factoranalysis. In identifying debt policy to apply proxy debt equity ratio and dividend policy, proxydividend yield was applied, then it was analyzed using difference test mean and test u mannwhitney. The empirical results showed that company having potency to grow high had higherdebt and lower dividend payment than companies having potency to grow low.